Ethno-cultural projects of contemporary Tatar youth in the context of maintaining ethnic identity - Aygul R. Mukhametzyanova (Историческая этнология, 2016)
This article analyzes contemporary national activism among Tatar youth, including the development of ethnic and cultural projects to popularize and spread Tatar language and culture. It considers the types and content of the projects, as well as the motivations of their authors. Young activists attach great importance to the Tatar language and seek effective methods for studying it and expanding the spheres in which it functions. The activists are likewise creating educational projects on Tatar history and culture. New ethnic cultural products are proposed: musical creations and visual forms. Tatar youth consider raising children with Tatar language and culture of great significance. Projects that consider Tatarness as a unique resource and create products for external users are appearing.